2021
DOI: 10.3389/fvets.2021.780731
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Supply of Ruminally-Protected Lysine and Methionine During Close-Up Period Enhances Immunity and Growth Rate of Neonatal Calves

Abstract: The objective of this study was to evaluate the effect of supplying ruminally-protected lysine (RPL), methionine (RPM), or the two in combination (RPML) to transition dairy cows on the immunity and performance of their offspring. Eighty heifer calves (n = 20 calves per group) were assigned to four treatments based on their dam diet; basal diet (CON), a basal diet with lysine [RPL, 0.33% of dry matter (DM)], a basal diet with methionine (RPM, 0.16% DM), or with the combination (RPML). Calves were fed colostrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Previous studies demonstrated that lymphocytes have a higher requirement for methionine, because in lymphocytes precursors such as choline and homocysteine are not met by methionine regeneration through the methionine cycle [ 34 , 35 ]. Wang Han et al also demonstrated that methionine supplementation increased the plasma IgG level in dairy cows [ 36 ]. Therefore, methionine levels should be more than the growth maintenance requirements of animals to meet the needs of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that lymphocytes have a higher requirement for methionine, because in lymphocytes precursors such as choline and homocysteine are not met by methionine regeneration through the methionine cycle [ 34 , 35 ]. Wang Han et al also demonstrated that methionine supplementation increased the plasma IgG level in dairy cows [ 36 ]. Therefore, methionine levels should be more than the growth maintenance requirements of animals to meet the needs of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…This research is a part of a large project to study the effect of ruminally protected amino acids on transition dairy cows and their neonatal calves. Cows, calves management, sampling, analysis procedures, and results were previously reported ( 18 , 29 , 30 ). Briefly, this study lasted from 3 weeks before calving until 5 months after calving (approximately 6 months), the study on the dairy cows contained two majors stages; (1) transition period (3 weeks before through 3 weeks after calving), (2) high milking period (from 22 to 150 days in milk), besides the trial on neonatal calves born from the transition cows that were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The cows were fed their respective diets starting at about 3 weeks [transition period, (25.0 ± 3.31 days) before the anticipated calving to 3 weeks post-calving (24.0 ± 3.31 days)]. A statistical power analysis was performed before the study using G–power 3.1 software ( 31 ), and power = 0.95, α = 0.05, and 0.32 effect size indicated a minimum group size of 100 cows, more details in our previous studies ( 18 , 30 ). Until the end of the first stage of the study (about 21 DIM), some cows were culled, diseased, sold, or died, and the cows removed from the herd for any reason were excluded from the statistical analysis [refer to our previous paper of Elsaadawy et al ( 18 )].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations